A Cross-Layer Optimization Approach for Energy Efficient Wireless Sensor Networks: Coalition-Aided Data Aggregation, Cooperative Communication, and Energy Balancing. (20th May 2007) - Gao, Qinghai; Zhang, Junshan; Shen, Xuemin (Sherman); Larish, Bryan
Abstract : We take a cross-layer optimization approach to study energy efficient data transport in coalition-based wireless sensor networks, where neighboring nodes are organized into groups to form coalitions and sensor nodes within one coalition carry out cooperative communications. In particular, we investigate two network models: (1) many-to-one sensor networks where data from one coalition are transmitted to the sink directly, and (2) multihop sensor networks where data are transported by intermediate nodes to reach the sink. For the many-to-one network model, we propose three schemes for data transmission from a coalition to the sink. In scheme 1, one node in the coalition is selected randomly to transmit the data; in scheme 2, the node with the best channel condition in the coalition transmits the data; and in scheme 3, all the nodes in the coalition transmit in a cooperative manner. Next, we investigate energy balancing with cooperative data transport in multihop sensor networks. Built on the above coalition-aided data transmission schemes, the optimal coalition planning is then carried out in multihop networks, in the sense that unequal coalition sizes are applied to minimize the difference of energy consumption among sensor nodes. Numerical analysis reveals that energy efficiency can be improved significantly by the coalition-aided transmission schemes, and that energy balancing across the sensor nodes can be achieved with the proposed coalition structures.